Targeting L-type amino acid transporter 1 in urological malignancy: Current status and future perspective - Sangjon Pae; Shinichi Sakamoto; Xue Zhao; Shinpei Saito; Takaaki Tamura; Yusuke Imamura; Tomokazu Sazuka; Yoshie Reien; Yuri Hirayama; Hirofumi Hashimoto; Yoshikatsu Kanai; Tomohiko Ichikawa; et al. (Elsevier, 2022)
Amino acid transporters are responsible for the uptake of amino acids, critical for cell proliferation. L-type amino acid transporters play a major role in the uptake of essential amino acids. L-type amino acid transporter 1 (LAT1) exerts its functional properties by forming a dimer with 4F2hc. Utilizing this cancer-specificity, research on diagnostic imaging and therapeutic agents for malignant tumors targeting LAT1 progresses in various fields. In hormone-sensitive prostate cancer, the up-regulation of L-type amino acid transporter 3 (LAT3) through the androgen receptor (AR) has been identified. On the other hand, in castration-resistant prostate cancer, the negative regulation of LAT1 through AR has been determined. Furthermore, 4F2hc: a binding partner of LAT1, was identified as the specific downstream target of Androgen Receptor Splice Variant 7: AR-V7. LAT1 has been suggested to contribute to acquiring castration resistance in prostate cancer, making LAT1 a completely different therapeutic target from anti-androgens and taxanes. Increased expression of LAT1 has also been found in renal and bladder cancers, suggesting a contribution to acquiring malignancy and progression. In Japan, clinical trials of LAT1 inhibitors for solid tumors are in progress, and clinical applications are now underway. This article will summarize the relationship between LAT1 and urological malignancies.